TAX TREATEMENT OF FARMERS IN THE REPUBLIC OF SERBIA - Cvjetković, Cvjetana; Veselinović, Janko; Nikolić, Ivica (Economics of Agriculture, 2018)
The subject of this paper is the tax treatment of natural persons that perform agricultural activities in the Republic of Serbia. The goal of the paper was to analyse norms related to the most important taxes that burden farmers, to assess their status in the Serbian tax system, as well as to formulate appropriate de lege ferenda propositions. The research showed that in many aspects farmers have privileged tax treatment due to the importance of agriculture in national economy, as well as their number and socialeconomic profle. Apart from the normative method, which was used predominantly, sociological, axiological and comparative methods were also used.